Auto-antibodies Profile in Children Infected with Visceral Leishmaniasis - Entsar Jabbar Saheb (Journal of Global Pharma Technology, 2018)
Visceral leishmaniasis (VL) is a parasitic infection caused by an intracellular growth of Leishmania spp. in macrophage cells. The autoimmune disorder is a condition takes place when the immune system produces antibodies which incorrectly attacked its own body tissues. VL has been involved as an effect or on the autoimmune aspect. This study was conducted to identify the auto antibodies profile in patients infected with VL. The presences of auto antibodies in 21 Iraqi children infected with VL were tested for laboratory autoimmune aspect. The highest percentage of seropositive in Leishmania patients was observed for anti-ds DNA, anti-Mi-2, anti-Ku and anti-PCNA antibodies (90.5%, 90.5% , 90.5% and 61.9%) respectively, while the lowest percentage was recorded for anti-Histone, anti-R0(RPP), anti-SS-A/Ro 52, anti-Scl 70, anti-Jo-1 antibodies (4.8%) while the auto antibodies (anti-SmD1, anti-SS-A/Ro-60, anti-SS-B/La, anti-CENP, anti-U1snRNP, anti-AMA M2, anti-PM/Scl) showed different profiles in Leishmania patients. These results provide evidence that VL can have an effective role in the production of the auto antibodies.Keywords: Children, Leishmania spp, Visceral leishmaniasis, Auto antibodies.